Application of Natural Polymers in Wound Dressings: Application of Natural Polymers in Wound Dressings - Shahzadi, Maria; Hassan, Taimoor; Saeed, Sana (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2022)
A plethora of synthetic, hybrid, and biological polymers are widely being used in medical supplications. A variety of polymers are helpful in our civic activities. Their peculiar chemical, physical, and biological properties are applicable in multiple domains of life from engineering to medicine. This review specifically addresses the novel polymers and their applications in wound dressings. It has been reported by the researchers that, natural polymers are not only playing tremendous roles in micro and macro medical-industry but they are also playing a remarkable role at nano levels as nano-drug carriers and being widely used in wound dressings in pharmaceuticals. In this editorial, we will give a brief introduction of polymers and how they are widely being used in medicinal interventions, it further sheds light on the prospects of polymers with an updated version.